2019
DOI: 10.1111/bdi.12825
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the clinical utility of two staging models for bipolar disorder

Abstract: Objective To assess the clinical utility of two staging models for bipolar disorder by examining distribution, correlation, and the relationship to external criteria. These are primarily defined by the recurrence of mood episodes (model A), or by intra‐episodic functioning (model B). Methods In the Dutch Bipolar Cohort, stages according to models A and B were assigned to all patients with bipolar‐I‐disorder (BD‐I; N = 1396). The dispersion of subjects over the stages was assessed and the association between th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 42 publications
1
14
0
Order By: Relevance
“…Patients were allocated to stage 2 (one mood episode), stage 3a (one mood episode with current residual symptoms), stage 3b (two mood episodes), or stage 3c (multiple recurrent mood episodes). In our previous study on bipolar outpatients, 30 we found clustering in stage 3c of this model, which could be refined by subdividing subjects in this stage into subgroups with a maximum of 5 episodes, 6 to 10 episodes and more than 10 episodes, following cut-off points previously defined by Berk et al and Magalhães et al 33,34 For model B, 24 subjects were assigned to a stage ranging from latent to stage IV, using a predetermined set of items from the Questionnaire for Bipolar Disorder (QBP, 32 Figure 1). Stages I to IV were assigned based on social, occupational, and psychological functioning (Global Assessment of Functioning (GAF) > or ≤ 80), current mood episode (yes or no), employment over the last year (yes or no), work limitations (present or not present), and limitations in functioning (present or not present).…”
Section: Staging Classificationmentioning
confidence: 96%
See 1 more Smart Citation
“…Patients were allocated to stage 2 (one mood episode), stage 3a (one mood episode with current residual symptoms), stage 3b (two mood episodes), or stage 3c (multiple recurrent mood episodes). In our previous study on bipolar outpatients, 30 we found clustering in stage 3c of this model, which could be refined by subdividing subjects in this stage into subgroups with a maximum of 5 episodes, 6 to 10 episodes and more than 10 episodes, following cut-off points previously defined by Berk et al and Magalhães et al 33,34 For model B, 24 subjects were assigned to a stage ranging from latent to stage IV, using a predetermined set of items from the Questionnaire for Bipolar Disorder (QBP, 32 Figure 1). Stages I to IV were assigned based on social, occupational, and psychological functioning (Global Assessment of Functioning (GAF) > or ≤ 80), current mood episode (yes or no), employment over the last year (yes or no), work limitations (present or not present), and limitations in functioning (present or not present).…”
Section: Staging Classificationmentioning
confidence: 96%
“…The influence of clinical characteristics on illness progression may be studied using staging models. In our current study, we are building on two previous studies 29,30 in which we verified the applicability of the two staging models by Berk et al 23 and Kapczinski et al 24 The current study investigates whether clinical profiles based on the characteristics found in previous studies, that is, familial loading, childhood abuse, age at onset, illness duration, comorbid psychiatric disorders, addiction, treatment resistance, and cognitive functioning are associated with illness progression as defined by the model from Berk et al 23…”
Section: Introductionmentioning
confidence: 99%
“…Participants were from the ORBIT RCT (experiencing “later stage” BD, defined as having experienced 10 or more lifetime mood episodes). Importantly, various episodic “cut points” have been used to identify later stage individuals in previous studies, for example, 5 and 10 episodes 1,14,15 . The ORBIT trial from which these data were drawn employed a conservative cut point of 10 episodes to best ensure participants were within later stage.…”
Section: Methodsmentioning
confidence: 99%
“…The field of BD research is in the midst of attempts to conceptualize progression in BD, with staging models proposed to describe key features and correlates of BD as this progresses. No model of clinical staging in BD has yet been validated with systematic empirical testing, however a number of studies recently have focused on the advancement of staging in BD (eg, 1‐3 ). In line with this, the current study aims to advance the understanding of stage of illness in BD, via an exploration of latent structures underpinning phenomenological experiences, and of clinically meaningful subgroups within the “later stage” of BD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation